THE EFFECTIVENESS OF USING PHOTOGRAPH SERIES TO INCREASE STUDENTS' SKILL OF WRITING A REPORT TEXT - Fajar, Ligawad; ., Sudarsono; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: This research was a pre experimental research with one group pretest posttest design. The purpose of this research was to investigate the effectiveness of using photograph series to increase students' skill of writing a report text to Year-8 students of SMPN 12 Sungai Rasau Singkawang in Academic Years 2015/2016. There were 4 classes for the Year-8, each of which consisted of 22 to 23 students. The participants of this research were 22 students of Class 8C. The data were collected with the written test measure the students ‘achievement of writing report text. The data was collected by measurement technique. The result of mean score of the students in pretest before treatment was 55.9 and the students mean score of posttest after treatment was 71.13. The research finding shows it is effective to teach writing using photograph series.   Keywords: The Effectiveness, Photograph Series, Writing Report Text   Abstrak: Penelitian ini merupakan penelitian pra eksperimental dengan satu kelompok desain pretest posttest. Tujuan dari penelitian ini adalah untuk mengetahui efektivitas penggunaan foto ber-seri untuk meningkatkan keterampilan siswa dalam menulis teks laporan kepada Tahun-8 siswa dari SMPN 12 Sungai Rasau Singkawang di Akademik Tahun 2015/2016. Terdapat  4 kelas untuk kelas-8, yang mana masing-masing terdiri dari 22 dan 23 siswa. Para peserta penelitian ini adalah 22 siswa dari Kelas 8C. Data dikumpulkan dengan tes mengukur kemampuan siswa dalam menulis teks laporan. Pengumpulan data dilakukan dengan teknik pengukuran. Hasil skor rata-rata siswa di pretest sebelum perlakuan adalah 55,9 dan skor rata-rata siswa di posttest setelah pelakuan adalah 71,13. Hasil penelitian ini menunjukkan bahwa efektif untuk mengajar menulis menggunakan foto ber-seri.   Kata kunci: Efektivitas, Foto ber-seri, Penulisan Teks Laporan